Contextuality in practical reason - Price, A. W. (Oxford : Oxford University Press, 2008)
A.W. Price explores the varying ways in which context is relevant to our reasoning about what to do. He investigates the role of context in practical inferences, practical judgements and the ascription of reasons for action.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Situation ethics